"It is kind of like a responsibility thing": transitional challenges in asthma medication adherence among adolescents and young adults. (4th May 2022) - Zaeh, Sandra E.; Lu, Monica A.; Blake, Kathryn V.; , ElizabethRuvalcaba; Ayensu-Asiedu, Christabelle; , Robert A. Wise; Holbrook, Janet T.; Eakin, Michelle N.
Abstract: Objective: Nonadherence to asthma medications is prevalent among adolescents and young adults (AYAs) with asthma, leading to worsened control of asthma symptoms and more frequent exacerbations. AYAs have unique developmental transitional challenges that may alter medication adherence. We aimed to use a socio-ecological framework to explore the effect of transitional challenges from adolescence to young adulthood on asthma controller medication adherence and to identify possible strategies to promote medication adherence. Methods: We conducted qualitative semi-structured interviews by phone with 7 adolescents (14 to 17 years), their respective caregivers, and 7 young adults (18 to 30 years). Participants were recruited from a respiratory clinical trial network and pulmonary clinics in 4 states at 6 different sites through convenience sampling. Interviews were audio recorded, transcribed and coded using thematic analyses. Results: Participants identified personal challenges affecting adherence to asthma medications during the transition from adolescence to young adulthood including responsibility for asthma self-management, understanding of asthma condition and severity, embarrassment, and life demands. Health systems factors including medication cost, challenges with insurance, difficulties obtaining refills, and difficulty with access to medications at school also impacted asthma medication adherence. Participants recommended adherence strategies including improved access to inhalers, incorporating asthma medications into daily routines, and using reminders. Conclusions: Focusing on the transitional challenges of AYAs during the time period from adolescence to young adulthood is necessary for supporting their asthma medication adherence and creating future interventions. Socio-ecological and systems factors should also be targeted for improved asthma medication adherence. Supplemental data for this article can be accessed online at https://doi.org/10.1080/02770903.2021.1897836 .